2015
DOI: 10.1002/ejsp.2144
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different procedures to arouse mortality awareness on various worldview dimensions

Abstract: An experimental study was carried out in order to explore two aspects of the terror management theory that have received little attention until now. The first objective was to see whether the different procedures to arouse mortality awareness have the same effects in certain dimensions included within the general construct of ‘worldviews’ (namely, commitment to life‐after‐death beliefs, Eurocentrism and xenophobia, European identity and the importance attached to the family and offspring in personal growth). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
2
19
0
3
Order By: Relevance
“…Even though the studies of the present research cannot rule out this possibility, results are consistent with past studies showing that various threats increase the use of different distal defense strategies via BIS-related emotions such as anxiety. One experimental setup, for instance, found that the effect of different types of mortality salience on worldview defense was mediated by negative affect ( Echebarria Echabe and Perez, 2016 ). Additionally, Webber et al (2015) demonstrated the pivotal role of emotions in worldview defense in their placebo study: When participants had the chance to attribute their anxiety to something other than threat, they showed less worldview defense afterward – indicating the importance of BIS-related variables in threat processing.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the studies of the present research cannot rule out this possibility, results are consistent with past studies showing that various threats increase the use of different distal defense strategies via BIS-related emotions such as anxiety. One experimental setup, for instance, found that the effect of different types of mortality salience on worldview defense was mediated by negative affect ( Echebarria Echabe and Perez, 2016 ). Additionally, Webber et al (2015) demonstrated the pivotal role of emotions in worldview defense in their placebo study: When participants had the chance to attribute their anxiety to something other than threat, they showed less worldview defense afterward – indicating the importance of BIS-related variables in threat processing.…”
Section: Discussionmentioning
confidence: 99%
“…Например, ряд исследований показал, что после напоминания о смерти евроамериканцы выражают более негативное отношение к афроамериканцам (Bradley et al, 2012); студенты американских университетов -к евреям (Cohen et al, 2009); шотландцы -к англичанам (Castano, 2004); немцы -к туркам (Pyszczynski et al, 2003); итальянцы -к немцам (Castano et al, 2002); жители европейских стран -к арабам и мигрантам (Das et al, 2009;Echebarria-Echabe, 2013;Echebarria-Echabe, Perez, 2016;Pan et al, 2017); арабы -к европейцам (Das et al, 2009); нигерийские студенты -к представителям народа хауса (Ezeh et al, 2017).…”
Section: влияние напоминания о смерти на отношение к социальным группамunclassified
“…Первый показатель -общие шкалы предрассудков, затрагивающие эмоциональный и когнитивный аспекты отношения (Cohen et al, 2009;Das et al, 2009;Echebarria-Echabe, 2013;Echebarria-Echabe, Perez, 2016;Pan et al, 2017). Второй показатель -наборы черт для измерения стереотипных представлений об аутгруппе (Castano et al, 2002;Castano, 2004;Pyszczynski et al, 2003).…”
Section: зависимые переменныеunclassified
“…Most popular prime involves asking participants to write down what they think happens when they die, and to jot down emotions aroused by thoughts of their own death. Some primes used death-related pictures; there have also been successful primes using terrorism-related stimuli (Echebarria Echabe & Perez, 2015). The goal of this study was to prime Terrorism as it is naturally encountered through the media; priming Mortality in the same format would enable comparisons between combination of MS and uncertainty in case of Terrorism.…”
Section: Designmentioning
confidence: 99%